Anti-ulcer mechanisms of polyphenols extract of Euphorbia umbellata (Pax) Bruyns (Euphorbiaceae). (15th September 2016) - Minozzo, Bruno Rodrigo; Lemes, Bruna Mikulis; Justo, Aline da Silva; Lara, Jheniffer Ellen; Petry, Victor Emanuel Kubaski; Fernandes, Daniel; Belló, Caroline; Vellosa, José Carlos Rebuglio; Campagnoli, Eduardo Bauml; Nunes, Otalíbio Castiglione; Kitagawa, Rodrigo Rezende; Avula, Bharathi; et al.
Abstract: Ethnopharmacological relevance: Euphorbia umbellata ( leitosinha ) is used in southern Brazilian folk medicine to treat gastric problems, as well as for its analgesic and anti-inflammatory properties. Aim of study: To evaluate the anti-ulcer effects of methanolic bark fraction (MF) against in vivo and in vitro assays, as well as an antioxidant, antibacterial and chromatographic study of this fraction. Materials and methods: In vivo anti-ulcer activity was performed using ethanol and indomethacin models with different MF concentrations (50, 100 or 200 mg/Kg). The stomachs of the animals were applied to histological evaluation, and the serum to evaluate the ABTS + radical capture. The 200 mg/Kg dose was used to analyze the mechanisms involved in antiulcerogenic properties of methanolic fraction. The in vitro activity was performed using several different antioxidant assays, in addition to anti- Helicobacter pylori and anti-urease experiments. The chromatographic study was carried out by LC-MS analysis. Results: Pharmacological investigation of the MF showed an anti-ulcer potential in ethanol and indomethacin in vivo assays. The material presented a high antioxidant activity for several oxidant in vitro systems (DPPH, ABTS +, O2 -, HOCl, TauCl and HRP), as well as an ABTS + capture increasing (7.5%) by the treated animals serum (when compared to the negative control). Prostaglandins, nitric oxide/ cyclic guanosine monophosphate pathway and involvement of the protein components of the glutathione complex are some of the mechanisms related with this potential anti-ulcer action. The histological examination of the stomachs of the animals showed that the MF also prevents local action of offensive agents. Chemical analysis using LC-QTOF-MS revealed the presence of ellagic and gallic acid derivatives and flavonols. Conclusion: The findings provide scientific basis to the ethnopharmacological purpose of the studied plant and the biological activities of MF of E. umbellata stem bark may be due to the presence of phenolic compounds. Graphical abstract: